High resolution paleo-monsoon records from peninsular Indian speleothems - Kaushal, N (2017)
The Indian Summer Monsoon is a major component of the global climatic system. Stalagmites have a proven ability to provide information of such monsoon systems. In this thesis, examination of cave records and field work provides a framework of the spatial and temporal distribution of stalagmites in peninsular India. Stable oxygen isotope records from stalagmites are supported by trace element records. An aragonite stalagmite from the west coast of India suggests that changes in growth surface can effect precipitation through time available for dissolved inorganic carbon removal. Calculation of empirical partition coefficients from the aragonite stalagmite indicates that U/Ca, Sr/Ca and P/Ca ratios may be paleo-aridity indicators through the process of Prior Aragonite Precipitation. There may also be source and/or temperature control on the partitioning of Sr/Ca into the aragonite stalagmite. These are the first trace element measurements for stalagmites from peninsular India and some of the few available from aragonite stalagmites. The δ18O composition of a calcite stalagmite from central India that grew from 3130 to 2100 years BP is consistent with the hypothesis that δ18O is controlled by air parcel trajectory and amount of rainout between source and cave site. P/Ca and U/Ca records from this stalagmite provide information on past rainfall conditions. Correlation analysis of δ18O, P/Ca and U/Ca indicates that rainfall amount was not the dominant control on δ18O composition at this cave site. Examination of a stalagmite that has diagenetically altered from aragonite to calcite shows that the δ18O system is extremely susceptible to diagenesis. Sr/Ca and U/Ca of the primary aragonite are retained in secondary calcite. Higher Mg/Ca ratios in secondary calcite compared to primary aragonite indicates that diagenetic fluid adds material to the primary carbonate. The variation in U-Th ages are caused by differential addition and losses of U and Th isotopes.